Negotiations Between Developers and Planning Authorities in Urban Development Projects. - Holsen, Terje (Taylor & Francis, 2020)
The purpose of this article is to examine how municipal authorities and developers conduct negotiations on detailed zoning plans for the implementation of brownfield transformation projects in the existing urban fabric. The study is based on four cases in Oslo, where municipal authorities and developers have negotiated the content of the zoning plans for the implementation of primarily residential development. The findings indicate that statutory and legally binding planning could work just as well as informal planning as the basis for integrative negotiations if statutory master plans are made more generic and allow for a necessary degree of flexibility. However, it seems that the parties’ ability to trust each other is even more fundamental for both the opportunity to establish integrative negotiations and for the outcome of the negotiations.
Keywords: Industriebrache; Flächenrecycling; Stadtentwicklung; Planungssystem; Flächennutzungsplan; Fallstudie